Ligasure™ Impact and Ligasure™ Small Jaw in Body Contouring after Massive Weight Loss: A New Perspective. Issue 3 (7th February 2022) - Pierazzi, Diletta Maria; Pica Alfieri, Edoardo; Cuomo, Roberto; Bocchiotti, Maria Alessandra; Grimaldi, Luca; Donniacuo, Aniello; Zerini, Irene; Nisi, Giuseppe
Abstract: Background: The most effective dissection technique for elevating flaps in body contouring is still controversial, particularly in high-risk massive weight loss (MWL) patients. LigaSure (Medtronic, Dublin, Ireland) is an energy device commonly used among different surgical specialties to reduce morbidity and improve outcomes. The aim of this study is to investigate the effectiveness of LigaSure Impact and LigaSure Small Jaw in body contouring after MWL compared with conventional technique. Material and methods: Patients who underwent abdominoplasty, mastopexy, brachioplasty and thigh lift after MWL at a single center from 1 December 2018 to 1 March 2020 were retrospectively reviewed. In each procedure patients were divided into two groups according to the dissection technique: LigaSure group and monopolar electrosurgery group. Patients characteristics, perioperative details and postoperative complications were evaluated. Results: Fourty-five patients underwent abdominoplasty, twenty-six mastopexy, twenty brachioplasty and sixteen medial thigh lift. Using LigaSure, operative time was longer in abdominoplasty and thigh lift, but shorter in mastopexy and brachioplasty. Although not statistically significant, the amount of blood and serum recorded from drains in the first 36 hours was reduced in LigaSure groups. Additional analgesic intake was reduced with LigaSure as well as postoperative subjective pain. In all body contouring procedures statistically significant difference was found in days of hospital stay favoring LigaSure groups. Complications occurred most frequently in control groups compared to LigaSure groups. Conclusion: LigaSure Impact and LigaSure Small Jaw may be beneficial in improving outcomes because they might reduce fluids drainage, analgesics intake, hospital stay and postoperative complications.